Inhibitory Effect of ATF3 Antisense Oligonucleotide on Ectopic Growth of HT29 Human Colon Cancer Cells - Ishiguro, Tatsuaki (Jpn J Cancer Res, 2000)
ATF3 is a transcription factor belonging to the Jun/Fos family whose mouse homologue (TI‐241) was isolated, using the differential screening method, from B16 mouse melanoma cells as a bloodborne metastasis‐associated gene. Here we show the tumorigenicity‐inhibiting effect of an antisense oligonucleotide designed to reduce the expression of ATF3 in HT29 colon cancer cells. HT29 cells were reported to metastasize to the skin after intravenous inoculation. The antisense oligonucleotide inhibited cell attachment to the collagen‐coated floor of the plates and invasion of HT29 cells in vitro, which are thought to be two important factors in the process of cancer metastasis and ectopic tumor growth. While the antisense oligonucleotide had no effect on cell growth of HT29 cells in vitro, mice that were inoculated subcutaneously with HT29 cells and treated with the antisense oligonucleotide survived longer than the control mice due to the inhibition of tumor growth in vivo.. These show that ATF3 plays an important role in the ectopic growth/metastasis of HT29 colon cancer cells.